Wooden on leadership - Wooden, John, 1910-2010 (McGraw-Hill, 2005)
"One of the lesser-known aspects of Wooden's career is the private notebooks in which he regularly recorded his observations, goals, and leadership concepts as they applied to basketball, success, and life. Wooden on Leadership draws from those personal notes to share practical and powerful leadership skills that anyone can use to improve performance and overcome self-imposed limitations."--Jacket